How companies win : profiting from demand-driven business models no matter what business you're in - Kash, Rick.; Calhoun, David (David L.) (New York : HarperBusiness, 2010)
Shows businesses how to find new customers and profits in a world of contracting markets and diminished consumer demand, outlining a business model that uses new tools and techniques to seek out areas of high-profit demand.
Includes bibliographical references and index.
Keywords: Organizational change; Organizational effectiveness; Customer relations; Consumer satisfaction; Customer services -- Management; Success in business